An innovative approach to creating business leaders: evidence from a case study. (18th September 2007) - Secundo, Giustina; Passiante, Giuseppina
The 21st century's competitive environment is challenging traditional management theories and requires business leaders able to meet the complexity of the new challenges. This entails a rethinking of the processes of education management. The aim of this paper is to present an innovative approach aimed at creating business leaders suitable for competing in the competitive landscape of the 21st century. The approach derives from an empirical study of the International Master in 'Business Innovation Leadership' organised by the e-Business Management Section (eBMS) of Scuola Superiore ISUFI?University of Lecce (Italy). The result is the creation of a new profile, the 'Change Manager and Business Engineer', capable of identifying and exploiting the distinctive potential of the new Information and Communication Technologies (ICTs) for reconfiguring traditional business contexts. We refer to this capability as ICT-driven Business Innovation Leadership, an evolution of traditional management education that integrates management studies with technological ones.